Association of adverse outcomes of intrahepatic cholestasis of pregnancy with zonulin levels. (18th August 2021) - Deniz, Cigdem Damla; Ozler, Sibel; Sayın, Fatma Kubra
Abstract: Our aim was to investigate serum zonulin levels in intrahepatic cholestasis of pregnancy (ICP) and to determine the usefulness of zonulin in ICP follow-up. A prospective case-control study was carried out which included 88 pregnant women (44 patients with ICP and 44 controls). Maternal serum samples obtained from all participants and zonulin levels were determined by enzyme-linked immunosorbent assay (ELISA). Compared with controls, women with ICP had significantly higher zonulin levels (mean 0.728 ± 0.520 ng/mL vs. 1.303 ± 0.63 ng/mL, p <. 001). According to the receiver operating characteristic (ROC) analysis performed for the predictive value of zonulin levels for ICP, the area under the curve (AUC) was 0.761 (95% CI: 0.661–0.860). Multivariable logistic regression analysis revealed serum zonulin levels was independently associated with adverse perinatal outcomes (OR = 1.278, 95% CI: 0.232–7.041), severity ICP (OR: 7.535, 95% CI: 1.597–13.553) and also unresponsiveness to treatment in ICP (OR: 4.178, 95% CI: 0.929–8.784). IMPACT STATEMENT: What is already known on this subject? Zonulin is a regulator protein that increases the intestinal permeability by modulating the intercellular tight junctions (TJ). It is the only physiological protein known to control intestinal permeability and damage of the intestinal barrier is one of the causes of absorption disorders, inflammation and autoimmunity. ICP is a relatively non-threatening condition to women but is linked with a higher risk of preterm delivery, foetal distress and foetal death. What do the results of this study add? This study showed that increased levels of zonulin are associated with adverse perinatal outcomes, severity of ICP and unresponsiveness to treatment in ICP. What are the implications of these findings for clinical practice and/or further research? Focussing on preservation of intestinal permeability may be an alternative preventive strategy to reduce the adverse perinatal outcomes and severity of ICP. Further longitudinal studies are needed to verify the relationships among zonulin levels and pregnancy-related diseases.